LncRNA FLVCR1‐AS1 acts as miR‐513c sponge to modulate cancer cell proliferation, migration, and invasion in hepatocellular carcinoma. Issue 7 (25th March 2018) - Zhang, Kunsong; Zhao, Zhenxian; Yu, Junfeng; Chen, Wei; Xu, Qiongcong; Chen, Liuhua
Abstract: In the present study, we aimed to search for dysregulated lnRNAs in Hepatocellular carcinoma (HCC) tissues, and analyze the relationship of its expression level with the clinicopathological feature and patient prognosis. The biological function of FLVCR1‐AS1, the identified lncRNA, in the process of HCC development, and progression was investigated in vitro and in vivo. The underlying molecular mechanism was further explored. We determined FLVCR1‐AS1 expression in HCC tissues and peri‐tumor tissues by bioinformatic analysis, qRT‐PCR, Northern blot and in situ hybridization. The relationship between FLVCR1‐AS1 expression level and prognosis was determined by analyzing clinical samples. The effects of FLVCR1‐AS1 knockdown on HCC cell proliferation, apoptosis, migration, and invasion were investigated by CCK8, FACS, and tanswell assay, respectively. Tumor xenograft model was used to determine the influence of down‐regulated FLVCR1‐AS1 on tumor growth and metastasis. lncRNA FLVCR1‐AS1 was extremely up‐regulated in HCC tissues and cell lines. FLVCR1‐AS1 expression level was positively correlated with tumor severity. FLVCR1‐AS1 knockdown remarkably inhibited HCC cell proliferation, migration, and invasion in vitro and in vivo while induced cell apoptosis. In mechanism, FLVCR1‐AS1 acted as a competitive endogenous RNAs to sponge miR‐513c which targeted the mRNA of MET for degradation. By directly sponging miR‐513c, FLVCR1‐AS1 increased MET expression in HCC, and then promoted HCC progression. It was demonstrated that FLVCR1‐AS1 played a positive role in HCC development and progression according to the study in its mechanism, function and clinical manifestation, so that it could be expected to become a new target in HCC prevention and treatment. Abstract : LncRNA FLVCR1‐AS1 was extremely up‐regulated in HCC tissues and cell lines. FLVCR1‐AS1 expression level was positively correlated with tumor severity. FLVCR1‐AS1 knockdown remarkably inhibited HCC cell proliferation, migration and invasion in vitro and in vivo while induced cell apoptosis.